PERAN SELF REGULATION DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SEBAGAI UPAYA MENYIAPKAN GENERASI EMAS 2045 - Sri Hapsari (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2017)
The purpose of this research is to determine the role of self regulation in enhancing the ability of creative thinking in social studies teaching and learning. Therefore, the author conducted a survey on junior high school in South Tangerang, Banten. Students ability to organize themselves into an important key in developing the ability to think creatively. Students will know what you want to achieve so that he has a conscious effort to focus the attention and the ability to complete the task. Ability is what is required by Indonesian golden generation because they will be dealing with a very complex challenge. The golden generation should be given so that the provision could be responsible for the lives of himself and his people.